To buy or to lie: Determinants of purchase intention of counterfeit fashion in Malaysia - Ong, Derek Lai Teik *; Chiang, Terrance Tong Seng *; Pung, Amanda Xin-Yi (Bucharest University of Economic Studies Publishing House, 2015)
In the competitive market of the fashion industry, counterfeit fashion has become prominent and also a great threat to the original brands in the market. The study seeks to investigate the factors that affect consumers' purchase intention towards counterfeit fashion products (CFP). Constructs of past experience of consumers, perceived risk, social influence, attitudes of consumers towards the purchase intention of counterfeit fashion products were explored through the distribution of 350 questionnaires. 245 usable date is analysed and the results showed that past experience and social influence have the most significant influential effect towards the purchase intention of CFP. The results also proved that consumers' attitude towards CFP have a mediating effect and gender moderates between past experience and purchase intention. This research discusses the implications towards authentic brand manufacturers in fashion industry and recommendations for future research studies, which will help researchers in conducting research more accurately